Pemberdayaan Ibu Rumah Tangga Melalui Budidaya Ikan dan Sayur Akuaponik dalam Ember di Desa Kedungbanteng Ponorogo - Yunaita Rahmawati; Silvia Dwi Russanti (Abdimas Indonesian Journal, 2021)
The covid-19 pandemic that has long been a ghost in real life. Many economic sectors such as MSMEs, farmers, traders, etc. experienced a lot of losses and decreased turnover, which had an impact on the economic downturn. The economic sluggishness was also felt by the majority of the people of Kedungbanteng village, Sukorejo sub-district, the majority of whom worked as rice farmers. So the researchers held activities to empower housewives through the cultivation of catfish and aquaponic vegetables in buckets. With the ability to grow vegetables, you can help save the cost of kitchen shopping materials amid the economic downturn that occurred during the COVID-19 pandemic. In this service, the ABCD method is used, namely by reviewing to find out the assets owned by an organization or community, so that it can carry out a change program that is expected to increase development in assets. From the results of the evaluation of activities carried out by the service, it can help save on food shopping for housewives in the midst of the covid-19 pandemic.